(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
This work presents the results of the development of the evaluation of the cocoa cacota (Theobroma cacao L.) CLON FEAR-05 looking for an alternative to the problem with organic waste, investigating some of the uses that these can have in the use to obtain activated carbon of different degrees of adsorption for uses such as: water decontaminants, solvent recovery, emission control, liquid discoloration, to obtain carbonaceous materials through chemical activation, tests were carried out at the Universidad de los Llanos, for this purpose carried out tests where the activation was done by means of different temperatures 600, 700 and 800 °C, finding in the determination of humidity for the C1 of 2.4693%, the C2 of 2.8748% and the C3 of 2.5790%, in the test carried out to determine the ash in each of the temperatures described above was C1 4.68%, C2 2.74% and C3 6.08% respectively, the tests submitted to the raw material to determine the volatile material that yielded a result of 62.36% for C1, 64.81% for C2 and 78.95% for C3; In addition, the C1 was 30.49% of the carbonaceous material, the C2 was 29.58% and the C3 obtained a lower value of 12.39% of fixed carbon. What can be deduced when determining the characteristics of the precursor material, allows to project the type of activated carbon to be theoretically obtained, because these characteristics are related to the quality and properties of the carbonaceous material, so it can be recommended in the use of the product. in the absorption of chemicals such as methylene blue, phenol and among others already mentioned above, since it is the greatest use that is being given to them with the investigations carried out.